The efficacy of SARS-CoV-2 antibody response after two dose mRNA vaccination in kidney and heart transplant recipients using a multiplex bead-based assay: Evaluating the factors affecting vaccine response - Steven J Forte; Angela J Toepp; Robert A Bray; David A Baran; Lauren T Gilgannon; Troy Williams; Shirui Chen; Hooman Sadr; Howard M Gebel; John M Herre; Thomas R McCune (Archives of Organ Transplantation - Peertechz Publications, 2022)
Background: The extent that which immunosuppressive factors contribute to the antibody response to SARS-Cov-2 vaccination in solid organ transplant patients is being better understood. This study examined antibody formation against the spike SARS-CoV-2 protein (SA) when full vaccinations were up to 2 doses and boosters were not recommended. Immunosuppressive factors that affected the vaccine responsiveness in a cohort of 100 kidney and 50 heart transplant patients were evaluated. This study utilized a novel assay to detect antibodies against 4 different domains of the spike protein and the nucleocapsid protein (NC) of the SARS-CoV-2 virus on a multiplex, bead-based platform. Positive SARS-COV-2 antibodies (SA) response required identification of the receptor-binding domain and one of the three other spike protein domains. Prior SARS-CoV-2 infection could be determined by the presence of positive NC.  Results: 150 patients were enrolled in the study (100 kidneys; 50 heart recipients). This study was performed when the Center for Disease Control and Prevention (CDC) recommended only two doses of Pfizer/BioNTech [BNT162b2] and Moderna [mRNA-1273 SARS-CoV-2] vaccine or 1 dose of Johnson & Johnson/Janssen [Ad26.COV2.S] vaccines for full SARS-CoV-2 vaccination in transplant recipients. Patients that reported a positive COVID-19 swab or had positive NC were excluded from the review because the prior infection may impact vaccine response (n = 134).  Conclusions: SA were identified in 48/134 patients (36%); 25/46 heart (54%) and 23/88 kidney transplant patients (26%) (P = 0.0012). For the patients on prednisone therapy 25/93 responded with SA (27%) while for patients not on prednisone therapy, 23/41 responded with SA (56%) (P = 0.0012). The dose of steroids (5mg a day or greater) at the time of vaccination did not adversely affect vaccine efficacy (p = 0.054). Of the patients using antimetabolite therapy, 36/113 responded with SA (32%) while 12/21 patients not on antimetabolites responded with SA (57%) (P = .027). Time since transplant was not found to affect the rate of SA production when populations were separated by type of organ transplanted. T-cell depletion induction method, calcineurin inhibitor use, and type of SARS-CoV-2 vaccine were not found to be statistically significant.